Ca(2+) Dependence of Volume-Regulated VRAC/LRRC8 and TMEM16A Cl(–) Channels - Centeio, Raquel (Front Cell Dev Biol, 2020)
All vertebrate cells activate Cl(–) currents (I(Cl)(,swell)) when swollen by hypotonic bath solution. The volume-regulated anion channel VRAC has now been identified as LRRC8/SWELL1. However, apart from VRAC, the Ca(2+)-activated Cl(–) channel (CaCC) TMEM16A and the phospholipid scramblase and ion channel TMEM16F were suggested to contribute to cell swelling-activated whole-cell currents. Cell swelling was shown to induce Ca(2+) release from the endoplasmic reticulum and to cause subsequent Ca(2+) influx. It is suggested that TMEM16A/F support intracellular Ca(2+) signaling and thus Ca(2+)-dependent activation of VRAC. In the present study, we tried to clarify the contribution of TMEM16A to I(Cl)(,swell). In HEK293 cells coexpressing LRRC8A and LRRC8C, we found that activation of I(Cl)(,swell) by hypotonic bath solution (Hypo; 200 mosm/l) was Ca(2+) dependent. TMEM16A augmented the activation of LRRC8A/C by enhancing swelling-induced local intracellular Ca(2+) concentrations. In HT(29) cells, knockdown of endogenous TMEM16A attenuated I(Cl)(,swell) and changed time-independent swelling-activated currents to VRAC-typical time-dependent currents. Activation of I(Cl)(,swell) by Hypo was attenuated by blocking receptors for inositol trisphosphate and ryanodine (IP(3)R; RyR), as well as by inhibiting Ca(2+) influx. The data suggest that TMEM16A contributes directly to I(Cl)(,swell) as it is activated through swelling-induced Ca(2+) increase. As activation of VRAC is shown to be Ca(2+)-dependent, TMEM16A augments VRAC currents by facilitating Hypo-induced Ca(2+) increase in submembraneous signaling compartments by means of ER tethering.